(untitled) - Molteno, Matthew Robert

Measuring fracture properties using digital image and volume correlation: decomposing the J-integral for mixed-mode parameters (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.